Justification of the dialog control method by energy efficiency - Доценко, Сергей Ильич (Technology audit and production reserves, 2014)
This paper proposes a method for modeling the dialog control of activities to ensure the rational use of energy. Method of model forming based on the methodology of ISO 9001 and ISO 14001. It was found that the formation of the methodology of control systems on these standards based on ensuring compliance of actual values of the process implementation effectiveness with its project values in the form of balanced relationship. It is also shown that in the case of the formation of the energy management system in the form of an automated control system, it should be classified as an interactive control system, or as a decision support system controlled by model. At the same time, it is proposed to use the activity factor model as a control model, which takes into account both process and resource factors for organizational and technological activities in this area. The architecture of this system is allowed to form on the base of the functional system developed by Academician P. K. Anokhin.